Relationship between dynamic expiratory time constant tau(edyn) and parameters of breathing cycle in pressure support ventilation mode - Čandík, Peter; Rybár, Dušan; Depta, Filip; Sabol, František; Kolesár, Adrian; Galková, Katarína; Török, Pavol; Doničová, Viera; Imrecze, Štefan; Nosáľ, Martin; Donič, Viliam (Physiological research, 2018)
Study of the relationship between ventilation parameters: monitored expiratory time constant - tau(edyn) and breathing - trigger frequency (f(trig)) and time of breathing cycle (T(cy)) are main goals of this article. Parameters were analyzed during last 4+/-2 h before weaning from ventilation in 66 patients ventilated in pressure support mode (PSV). We have found out, that there exist mathematical relationships, observed during adequate gas exchange, yet not described. Monitored parameters are represented by tau(edyn), f(trig) and T(cy). The analysis showed close negative correlation between T(cy) and f(trig) (R(2)=0.903). This implies that each increasing of tau(edyn) causes decreasing of f(trig) and vice versa. The calculation of regression equation between tau(edyn) and T(cy) outlined that T(cy) = 5.2625 * tau(edyn) + 0.1242 (R(2)=0.85). Regulation of respiratory cycles by the respiratory center in the brain is probably based on evaluation of tau(edyn) as the tau(edyn) probably represents a regulatory element and T(cy) regulated element. It can be assumed, that respiratory center can optimize the work of breathing in order to minimize energy in system patient + ventilator. The unique relationship, described above could be useful in clinical practice for development of new ventilation modes.
Keywords: Ventilator Weaning; Exhalation; retrospektivní studie; Humans; lidé středního věku; Middle Aged; Time Factors; mužské pohlaví; Positive-Pressure Respiration; Respiratory Mechanics; umělé dýchání; vydechnutí; časové faktory; Respiration, Artificial; ženské pohlaví; odpojení od ventilátoru; lidé; ventilace umělá s výdechovým přetlakem; Aged; mechanika dýchání; Male; senioři; Retrospective Studies; Female